Storytelling: Developing stories and experiences more on food tourism - Handayani Rahayuningsih; Anik Nuryani; Fennyta Christa Naomi; Hanum Pramudyasmara Jati (International Journal of Applied Sciences in Tourism and Events, 2025)
Food tourism has become one of the main attractions in the era of globalization, especially in Indonesia, with the growth of the food tourism sector continuing to develop. However, ordinary food tourism experiences are no longer sufficient to captivate tourists who are increasingly seeking deep and memorable experiences. Therefore, this research aims to develop storytelling scripts in culinary tourism so that tourists can gain a deeper and more memorable understanding of local gastronomy. In this context, the study focuses on the development of storytelling for food tourism in Kemiriombo, Kulon Progo. The research method used was a qualitative approach with data collection techniques such as participatory observation, in-depth interviews, documentation, and literature studies. The research results in a storytelling script that contains the connections between food and the culture and traditions of the Kemiriombo community, raw materials, processing methods, nutritional content, and the differences between traditional food in Kemiriombo and similar foods in other regions. This is intended so that when visitors participate in food tourism activities in Kemiriombo, they not only experience tasting traditional food but also gain knowledge about the connections between the cuisine and the traditions and cultures that develop in the community, the differences between traditional Kemiriombo food and similar foods in other areas, and also gain additional experiences through sourcing raw materials and processing the food.